EOLP-04. A CALL TO ACTION TO INCREASE ACCESS TO POST-MORTEM BRAIN TUMOR DONATIONS: GIFT FROM A CHILD. (14th November 2022) - Lyons, Nicole; Waanders, Angela; Williams, Melissa; Nazarian, Javad; Eze, Augustine; Bornhorst, Miriam; Frenkel, Elizabeth; Mason, Jennifer; Minturn, Jane E; Koptyra, Mateusz; Monje, Michelle; Hysinger, Jared; et al.
Abstract: Implementation of access to donate post mortem tissue among pediatric brain tumor patients remains a challenge[DSM1] . Previous attempts to develop a post-mortem network have been jeopardized by barriers such as a lack of education, logistical coordination of donation, and difficulties effectively communicating the benefit of post-mortem donations to families. [CC2] Utilizing feedback from patients' families, clinicians, and researchers, standard operating procedures (SOP) were developed and utilized by six "tissue navigators" (TN) working across institutions. Tissue navigators are critical in implementation of access to donate as they serve as a liaison between patients' families and clinical team to ensure post-mortem tissue is procured correctly and respectfully. From 2018 through 2021, there has been an increase in donations, which has led to establishment of tumor cell cultures translating rapidly to clinical development, and a growing network of centers participating in GFAC procedures. Donations have been facilitated at over 75 institutions. GFAC has coordinated 146 donations in this 3-year launch timeframe, with nearly half from families outside GFAC's primary institutional network. Barriers to implementation were addressed with the design of GFAC's SOPs, which lead to the successful implementation of access to donation. GFAC is developing CME training for clinicians and researchers to address communication of post-mortem donation, continuing awareness campaigns with collaborators in the field, advocating for families to receive feedback on the donation, and expanding on the SOPs as more is learned from clinicians and families.